PANCASILA SOCIALISM AND CHINESE SOCIALISM: A COMPARATIVE ANALYSIS BETWEEN RELIGIOUS AND MATERIALIST APPROACHES IN THE FORMATION OF STATE IDEOLOGY - Widianto, Adita Taufik; Widyasari, Riztika (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This article aims to comparatively analyze the characteristics of the state ideologies of Indonesia and China, especially between Pancasila Socialism and Chinese Socialism, based on religious and materialist approaches. The main focus of the research is to identify the historical foundations, philosophical values, and practical implications of both ideologies in shaping the policy direction and national identity of each country. This research uses a qualitative approach with a literature study method, through content analysis of scientific literature in the form of books, academic journals, and valid and relevant official state documents. The results of the analysis show that Pancasila Socialism is religious-humanistic, emphasizing the moral principles of divinity, humanity, and deliberation within the framework of cultural plurality. In contrast, Chinese Socialism is built on the basis of historical materialism and the centralization of the Communist Party's power, which emphasizes development efficiency and political stability. Although paradigmatically different, both ideologies have a strategic function as a social glue and a guideline for national development amidst global challenges. This finding emphasizes the importance of revitalizing state ideology contextually and participatively in order to remain relevant in the dynamics of the times